NEUROMIELITIS OPTIK DENGAN ANTIBODI IGG-AQP4 SERONEGATIF - Astra Dea Simanungkalit; Vivien Puspitasari (PERDOSNI, 2021)
Optic neuromyelitis (NMO), also known as Devic’s disease, is an autoimmune disease that results in recurrent demyelination of the central nervous system, particularly the optic nerve and spinal cord. The IgG antibody is an antibody that has high specificity for NMO-SD and plays an important role in the disease course. However, in a minority of cases, there are patients with NMO-SD with seronegative results. This article reports a case of a woman with an NMO-SD diagnosis without IgG-AQP4 antibodies. Keywords: Devic’s disease, IgG-AQP4, neuromyelitis optic, seronegative NMO